Rare postoperative delayed malignant hyperthermia after off-pump coronary bypass surgery and brief review of literature - Monish S Raut; Sibashankar Kar; Arun Maheshwari; Ganesh Shivnani; Arun Kumar; Elvin Daniel; Sandeep Joshi; Amit Motihar; Priyanka Gupta (Annals of Cardiac Anaesthesia, 2016)
Postoperative malignant hyperthermia (MH) is a very rare phenomena. It is generally observed within less than an hour after discontinuation of the anesthetic trigger. Present case describes rare delayed postoperative presentation of MH after off-pump coronary bypass surgery. Prompt recognition and immediate treatment with dantrolene can effectively treat the fatal syndrome. Family education and genetic counseling should be encouraged.